The Effectiveness of Amitriptyline and Gabapentin in Treating Pomeranians with Chiari-like Malformation and/or Syringomyelia - Ramona ter Maat; Kathelijn van Heusden; Larissa Hoogervorst-Spek; Marta Płonek; Paul J. J. Mandigers (Animals)
Background: Chiari-like malformation (CM) and syringomyelia (SM) are commonly observed disorders in the Pomeranians. Both disorders can lead to pain and diminish quality of life to varying extents. In veterinary medicine, affected dogs are often treated with gabapentin or pregabalin, which contrasts with human medicine, where the tricyclic antidepressants amitriptyline and nortriptyline are the first-choice treatments. Methods: affected dogs were treated with either amitriptyline or gabapentin. If a pre-syrinx was present, furosemide was also added. Owners were asked to score the clinical signs they observed (ORCS). Results: 90 Pomeranians were included, of which 62 received amitriptyline and 28 received gabapentin. Adding furosemide did not have an influence on the outcome. A logistic regression analysis with the number of ORCS, duration of ORCS, treatment (amitriptyline or gabapentin), and outcome (responder or non-responder) as the dependent variable revealed that the number of ORCS had an Odds of 1123 (p = 0.03). Duration of the ORCS (Odds 1.027; p = 0.45) and treatment group had a low influence (Odds 1.258; p = 0.65). Conclusions: In this study, amitriptyline demonstrated a moderate, though not statistically significant, more favorable effect on CM/SM pain compared to gabapentin. Adding furosemide to either of these two treatments did not influence the outcome. The outcome for dogs affected by CM/SM is not influenced by MRI grading; however, the number of ORCS and a longer duration negatively impact the outcome. A dose of 1 to 2 mg/kg body weight of amitriptyline administered twice daily proved to be more effective in several dogs.